PENGAWASAN PEMANFAATAN ZAKAT PRODUKTIF BAGI MUSTAHIQ DI KECAMATAN PAUH LIMAUMANIS KOTA PADANG - Nora Zulvianti; Rahima Zakia; Topan Mardizam (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2022)
As one of the Five Pillars of Islam, zakat is a religious duty for all Muslims. Zakat is a number of assets owned by Muslims that must be issued when it reaches the nisab. The distribution of zakat must be monitored. supervision of productive zakat by the management of the National Amil Zakat Agency (BAZNAS) of Padang City in the early days of activities is still often carried out. However, lately, there has been no supervision until now. The purpose of this research is to describe the supervision of productive zakat utilization for mutahiq in Pauh Limaumanis District, Padang City. This research is field research. The method used is a qualitative method. This type of research is descriptive. The findings of this study are that the Padang City Amil Zakat Agency (BAZNAS) supervises the utilization of productive zakat for mustahiq in Pauh Limaumanis District, Padang City.